(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
By taking advantage of the best characteristics of wood, modern production methods can offer hard wearing and ecological solutions in industrial construction, house building, machinery construction, furniture manufacturing, transport and many other industries. Laser cutting process is an alternative choice to prepare the final shape of wood parts. Materials like wood have good laser light absorption of wavelength 10600 nm. In this paper a CO2 laser system with a maximum continuous-wave output power of 150 W is described and used in studying laser cutting process of wood materials. Cut depth is evaluated with variation of values of laser power and cutting speed. Additionally, optimal values of parameters for laser cutting of different wood plate thicknesses are determined and graphs are created showing the results.